PKM Peran Administrasi dalam Pembangunan di Kelurahan Klabulu: Community Service The Role of Administration in Development in the Klabulu Village - Rusdi Rusdi; Ana Lestari; Nur Hidaya; Supriadi Supriadi (LP3M Universitas Muhammadiyah Sorong, 2023)
The role of the apparatus in the implementation of administration for the implementation of government tasks on development can affect the success or failure of national development goals. The orderly role of administration in supporting the success of development in Klabulu Village is one of the efforts to realize a state apparatus that is able to support the smooth and integrated implementation of the duties and functions of state governance and development. Klabulu sub-district has experienced various kinds of obstacles related to the implementation of administration and so far the administrative role in Klabulu sub-district has been held for quite a long time. The results of community service show that the role of administration in supporting the success of development in Klabulu Village is quite good